Trends in Cancer Treatment Service Availability Across Critical Access Hospitals and Prospective Payment System Hospitals - Hung, Peiyin; Shi, Kewei; Probst, Janice C; Zahnd, Whitney E; Zgodic, Anja; Merrell, Melinda A; Crouch, Elizabeth; Eberth, Jan M (Medical care, 2022)
Rural residents experience worse cancer prognosis and access to cancer care providers than their urban counterparts. Critical access hospitals (CAHs) represent over half of all rural community hospitals. However, research on cancer services provided within CAHs is limited. The objective of this study was to investigate trends in cancer services availability in urban and rural Prospective Payment System (PPS) hospitals and CAHs. Retrospective, time-series analysis using data from 2008 to 2017 American Hospital Association Annual Surveys. Multivariable logistic regressions were used to examine differential trends in cancer services between urban PPS, rural PPS, and CAHs, overall and among small (<25 beds) hospitals. All US acute care and cancer hospitals (4752 in 2008 to 4722 in 2017). Primary outcomes include whether a hospital provided comprehensive oncology services, chemotherapy, and radiation therapy each year. In 2008, CAHs were less likely to provide all cancer services, especially chemotherapy (30.4%) and radiation therapy (2.9%), compared with urban (64.4% and 43.8%, respectively) and rural PPS hospitals (42.0% and 23.3%, respectively). During 2008-2017, compared with similarly sized PPS hospitals, CAHs were more likely to provide oncology services and chemotherapy, but with decreasing trends. Radiation therapy availability between small PPS hospitals and CAHs did not differ. Compared with all PPS hospitals, CAHs offered fewer cancer treatment services and experienced a decline in service capability over time. These differences in chemotherapy services were mainly driven by hospital size, as small urban and rural PPS hospitals had lower rates of chemotherapy than CAHs. Still, the lower rates of radiotherapy in CAHs highlight disproportionate challenges facing CAHs for some specialty services.